Nitrous Oxide Emissions from Smallholders’ Cropping Systems in Sub-Saharan Africa - Shaankua E. Lemarpe; Collins M. Musafiri; Joseph M. Macharia; Milka N. Kiboi; Onesmus K. Ng’etich; Chris A. Shisanya; Jeremiah Okeyo; Elizabeth A. Okwuosa; Felix K. Ngetich (Advances in Agriculture)
Increased concentration of atmospheric nitrous oxide (N2O), a potent greenhouse gas (GHG), is of great concern due to its impact on ozone layer depletion leading to climate change. Ozone layer depletion allows penetration of ultraviolet radiations, which are hazardous to human health. Climate change culminates in reduced food productivity. Limited empirical studies have been conducted in Sub-Saharan Africa (SSA) to quantify and understand the dynamics of soil N2O fluxes from smallholder cropping systems. The available literature on soil N2O fluxes in SSA is limited; hence, there is a pressing need to consolidate it to ease mitigation targeting and policy formulation initiatives. We reviewed the state of N2O emissions from selected cropping systems, drivers that significantly influence N2O emissions, and probable soil N2O emissions mitigation options from 30 studies in SSA cropping systems have been elucidated here. The review outcome indicates that coffee, tea, maize, and vegetables emit N2O ranging from 1 to 1.9, 0.4 to 3.9, 0.1 to 4.26, and 48 to 113.4 kg N2O-N ha-1 yr−1, respectively. The yield-scaled and N2O emissions factors ranged between 0.08 and 67 g N2O-N kg−1 and 0.01 and 4.1%, respectively, across cropping systems. Soil characteristics, farm management practices, and climatic and environmental conditions were significant drivers influencing N2O emissions across SSA cropping systems. We found that site-specific soil N2O emissions mitigation measures are required due to high variations in N2O drivers across SSA. We conclude that appropriate fertilizer and organic input management combined with improved soil management practices are potential approaches in N2O emissions mitigation in SSA. We recommend that (i) while formulating soil N2O emissions mitigation approaches, in SSA, policymakers should consider site-specific targeting approaches, and (ii) more empirical studies need to be conducted in diverse agroecological zones of SSA to qualify various mitigation options on N2O emissions, yield-scaled N2O emissions, and N2O emission factors which are essential in improving national and regional GHG inventories.